High-frequency seafloor acoustic backscatter from coastal marine habitats of Australia. - Parnum, Iain; Gavrilov, Alexander (Acoustical Society of Australia, 2012)
Backscatter strength versus incidence angle has been measured from a variety of seafloor types from Australian coastal waters using a Reson Seabat 8125 multibeam echo-sounder (MBES) operating at 455 kHz. MBES surveys were carried out at six sites around Australia (between 2004 and 2006). Seafloor habitats surveyed in this study included: seagrass meadows, rhodolith beds, coral reef, rock, gravel, sand, muddy sand, and mixtures of those habitats. The highest backscatter strength was observed not only for the hard and rough substrate, but also for marine flora, such as rhodolith and seagrass. The main difference in acoustic backscatter from the different habitats was the mean level, or angle-average backscatter strength. However, additional information was also obtained from the rate of change (or slope) of backscatter strength with incidence angle. Overall, analysis of MBES backscatter data found at least six different seafloor habitats could be identified, in descending order of their average backscatter strength: 1) Rhodolith, 2) Coral, 3) Rock, 4) Seagrass, 5) sand-dominated bare (i.e. no epibenthic cover) sediment, 6) mud-dominated bare (i.e. no epibenthic cover) sediment.